Literacy world: literacy skills big book c stage 4 fiction - Lockwood, M. J. (Heinemann Educational England, 1999)
The "Literacy Skills Big Book C" is a resource aimed at enhancing early literacy skills for young learners. It offers a variety of engaging stories, activities, and illustrations designed to support reading comprehension, phonics, and vocabulary development. The large format makes it ideal for group settings, allowing teachers to read aloud and interact with children effectively. With a focus on encouraging participation and fostering a love for reading, this big book serves as a valuable tool for educators and parents alike, helping children build essential literacy skills in a fun and interactive way.